The effect of public pensions on women's labor market participation over a full life cycle - Virginia Sánchez Marcos; Carlos Bethencourt (Quantitative Economics, 2018)
Spousal and survivor pensions are two important provisions of the US Social Security pension system. In this paper, we assess the impact of these benefits on the female employment rate in the context of a full life-cycle model in which households decide on female labor supply and savings. One important aspect of our model is that we allow for returns to labor market experience so that participation decisions affect not only current earnings and Social Security pension eligibility but also future earnings. We quantify the effect on female labor supply and on household inequality of (i) removing spousal benefit, (ii) removing both spousal and survivor pension benefits, and (iii) extending from 35 to 40 the number of periods of the working career that are considered when calculating the retired worker's pension. We find that reforms (i) and (ii) significantly increase female employment throughout the life cycle, whereas reform (iii) has a very mild effect. The effect of (ii) on income inequality in older household is large, whereas the effect on consumption inequality is small. All three reforms have substantial effects on Social Security expenditure and fiscal revenues.
Keywords: D15; H55; J22; J24; 330; Social Security; Spousal and Survivor Benefits; Women's Labor Market Participation